Enhancing Students’ Self-Development Through Public Speaking Training: A Joint University Initiative (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Public speaking is a crucial competence for student self-development, strengthening personal confidence, academic clarity in expressing ideas, and professional competitiveness. However, many students continue to face challenges in oral communication, including low confidence, difficulty structuring arguments, and anxiety, often due to limited practical training. To address this gap, a joint community service program between Universitas Pendidikan Indonesia (UPI) and Universitas Muhammadiyah Yogyakarta (UMY) was implemented through a one-day workshop that combined core material delivery with guided practice. A pre-training and post-training questionnaire focusing on student perceptions was administered to twenty-one students to assess the effectiveness of the training. Results indicate a noticeable shift in students’ perceptions, with many reporting greater confidence in public speaking as well as better knowledge of how to structure stronger argumentation and delivery after attending the training. They valued the opportunity to connect theoretical input with guided practice, expressed highly positive feedback, and emphasized the importance of extending such training to a wider group of students. Overall, the program highlighted the potential of collaborative public speaking training and underscored the value of such community service in shaping future initiatives for broader community impact.